Conservative management versus surgical drainage in pancreatic pseudocyst - Almaihan, Abdullah; Matar, Ahmed; Murshid, Eman; Al-Ostaz, Sama; Shebly, Ahmed; Miftah, Mohammed; Alsaif, Eman; Alzaher, Doaa; Alyami, Hadi; Al-Ajmi, Fetoun (International Surgery Journal, 2018)
Pancreatic pseudocyst is not an uncommon complication of acute or chronic pancreatitis. It often presents with persistent abdominal pain and tenderness after the resolution of pancreatitis. Two lines of management are available for treatment of pancreatic pseudocyst: conservative management and surgical drainage. Conservative management is preferred in small-sized, asymptomatic, and short-lasting pseudocysts, whilst surgical management is often indicated when the cysts are larger in size, symptomatic, long-lasting, or when complications occur. Overall, 50% of cysts resolve spontaneously and only require conservative management, whilst surgical management is indicated for prevention of potential complications. This article will review and discuss in detail and compare between conservative management and surgical drainage of pseudocyst as regards indications, advantages, disadvantages, outcomes, and complications.